Reduction of vibration and acoustic noise in permanent magnet synchronous motor by optimizing magnetic forces. (1st September 2018) - Lin, Fu; Zuo, Shu-Guang; Deng, Wen-Zhe; Wu, Shuang-Long
Abstract: Two methodologies are proposed in this paper to reduce electromagnetic vibration and noise of permanent magnet synchronous motor. A multiphysics model is firstly established to predict the vibration and noise. Experimental tests are conducted to validate the model. Then, the source of the vibration and noise peaks from calculated and tested results is located. Two methodologies are proposed to mitigate this source. One is by reducing its amplitude through adjusting slot opening width and magnet shape. The other is by changing the phase of the specific force harmonic along the axial direction through stepwise or continuous magnet skewing. The optimum skewing angle is analytically derived. Based on the validated multiphysics model, optimizations under different methods are compared. It is found that considerable reductions of noise can be achieved by reducing low space harmonics of radial force. In particular, to reduce the noise over a wide frequency band, magnet skewing is a better solution than optimizing slot opening width and magnet shape.